2018
DOI: 10.1001/jama.2018.13201
|View full text |Cite|
|
Sign up to set email alerts
|

Five-Year Follow-up of Antibiotic Therapy for Uncomplicated Acute Appendicitis in the APPAC Randomized Clinical Trial

Abstract: IMPORTANCE Short-term results support antibiotics as an alternative to surgery for treating uncomplicated acute appendicitis, but long-term outcomes are not known. OBJECTIVE To determine the late recurrence rate of appendicitis after antibiotic therapy for the treatment of uncomplicated acute appendicitis. DESIGN, SETTING, AND PARTICIPANTS Five-year observational follow-up of patients in the Appendicitis Acuta (APPAC) multicenter randomized clinical trial comparing appendectomy with antibiotic therapy, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
350
3
28

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 383 publications
(399 citation statements)
references
References 21 publications
18
350
3
28
Order By: Relevance
“…In this cohort, already the majority of cases (64%) was treated in general hospitals and, assuming equivalent outcomes, this may be further encouraged. Non-operative treatment of appendicitis has also been proposed to be an economical choice [17], at no compromise in safety according to several recent studies [11,49,50]. Patients treated non-operatively were excluded from this study, and the DBC reimbursement system does not allow for discrimination of operating costs from admission day costs.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, already the majority of cases (64%) was treated in general hospitals and, assuming equivalent outcomes, this may be further encouraged. Non-operative treatment of appendicitis has also been proposed to be an economical choice [17], at no compromise in safety according to several recent studies [11,49,50]. Patients treated non-operatively were excluded from this study, and the DBC reimbursement system does not allow for discrimination of operating costs from admission day costs.…”
Section: Discussionmentioning
confidence: 99%
“…In children, there are no available long-term data. In adults, a recent 5-year follow-up of the APPAC trial showed that 27% of patients had undergone appendectomy at 1 year and 39% at 5 years, indicating that recurrences occur also in long term [34].…”
Section: Limitationsmentioning
confidence: 99%
“…Computed tomography confirmed that uncomplicated colonic diverticulitis 13) and uncomplicated appendicitis 14) can be treated without a source control procedure. Although a recent RCT 12) demonstrated that observational treatment without antibiotics can be appropriate in patients with uncomplicated diverticulitis 13) , omission of antimicrobial therapy should be indicated only in selected patients who are low-risk 2) .…”
Section: B Patients Without a Source Control Proceduresmentioning
confidence: 87%